Arabic Language Education Discourse Based on MBKM Curriculum: A Systematic Literature Review - Wahyu Hanafi Putra; Haruna Abubakar Haruna; Kunti Nadiyah Salma; Anisatu Thoyyibah (Universitas Islam Negeri Jurai Siwo Lampung, 2026)
Background: Arabic Language Education (ALE) in Indonesia is undergoing a paradigm shift under the Merdeka Belajar–Kampus Merdeka (MBKM) framework, which emphasizes flexible, outcome-oriented, and collaborative learning. However, scholarly discourse on its interpretation and implementation remains fragmented, especially regarding pedagogical adaptation, stakeholder readiness, and inclusivity. Research Objectives: This study aims to analyze the dominant discourse of ALE within the MBKM curriculum framework and to identify gaps that require further scholarly attention. Methodology: The study employed a Systematic Literature Review (SLR) design, selecting total of 25 peer-reviewed journal articles published by Indonesian domestic publishers between 2020 and 2024 based on rogorous inclusion and exclusion criteria. The review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework and involved digital library searches through Open Journal Systems, keyword identification, and keyword operationalization. Data were analyzed through quality assessment, relevance screening, and thematic classification to ensure consistency, validity, and reliability in article selection and interpretation. Results: The findings reveal that the dominant discourse on MBKM-based Arabic Language Education centers on opportunities and challenges, as well as teacher and student competencies. These themes are closely related to curriculum document analysis, stakeholder perceptions, students’ knowledge development, and the acceleration of MBKM implementation in both higher education and Islamic boarding schools. Gender equity, however, remains underexplored. Unique Contribution: This study maps the evolving landscape of MBKM-based ALE while highlighting the limited integration of gender-responsive perspectives, an issue rarely foregrounded in previous reviews. Conclusion: MBKM has broadened the orientation of Arabic Language Education toward more adaptive and collaborative learning, yet its discourse remains concentrated on implementation and competency issues. Recommendations: Future studies should develop empirical and policy-oriented investigations on gender-responsive MBKM practices through inclusive learning materials, character education, diverse learning activities, and stronger collaboration with governmental and educational institutions.